Analisis Dampak Keberadaan Hewan Ternak Milik Warga Sekitar Bandara Bagi Keselamatan Penerbangan di Bandar Udara Internasional Zainuddin Abdul Madjid Lombok - Ali Akbar Pratama; Kifni Yudianto (MES Management Journal, 2024)
This research aims to determine the causes, impacts and solutions for the presence of livestock belonging to local residents at Zainuddin Abdul Madjid Lombok airport. This topic was raised to examine news and news as well as events that occurred in the field regarding this topic. A number of accurate and factual data were collected through a process using qualitative research methods, including interviews with informants, observations by researchers and documentation during the research. The results of the research explain that the cause of livestock entering the airport area, namely in the perimeter area and the approach light system area, is because there are abundant food sources for livestock so that livestock owners graze their livestock in the airport area, apart from the condition of the existing guardrails. it is no longer feasible because the land contour is unstable and most of the boundary fences with residents' land are missing. This has an impact on concerns about the potential that will disrupt activities and endanger flight safety. Then airport officers and managers collaborated with the government and local officials to carry out mass evictions and provide outreach to owners, including livestock keepers, as a mitigation and solution to this problem